Pengajaran Bahasa Arab di Madrasah dan Sekolah - Syamsuddin Asyrofi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2017)
Method in teaching-learning process is very important, especially in learning foreign language, for instance Arabic, as a tool achieve the determined goal. Learning method is always changing from time to time in line with the developmentof the epoch. It is not surprised that new methods of learning are developved rapidly. However, the new methods are usually created as the “ reaction” to the old methods that have been used before. The new methods are often claimed as the best method to be used, Nevertheless, a method is not viewed as good or not, but a method is viewed as whether it is proper or not for certain condition. Every method has its own advantages that can be used by considering the existing condition